Associations Between the Big Five Personality Traits and a Medical School Admission Interview - Lourinho, I (2016)
INTRODUCTION: Personality has became popular in medical student's selection. However, few research exists about the association between the big five personality traits and the existent medical school selection tools. Our aim was to study which personality traits were selected by a medical school admission interview. MATERIAL AND METHODS: One hundred ninety four graduate applicants that had applied to the Faculty of Medicine of the University of Porto through the graduate entry approach, after ranked on previous achievement, were interviewed between the academic years of 2011 and 2013. From these, 181 (93.3%) answered to the NEO Five-Factor Inventory that assesses high order personality traits of openness to experience, conscientiousness, extraversion, agreeableness and neuroticism. Admission interview corresponded to the second phase of the seriation process. Every applicant was interviewed and scored by three interviewers on seven dimensions asesssed by Lickert scale (1-10). Interview score was the sum of the dimensions. Linear mixed effects model and respective regression coefficients were used to estimate the association between personality traits from each interviewer's score. Final models were adjusted for gender, interviewers and previous achievement. RESULTS: Openness to experience (Beta = 0.18: CI 95%: 0.05; 0.30) had the strongest association with interview score followed by the interaction effect between the extraversion and conscientiousness traits (Beta = 0.14; CI 95%: 0.02; 0.25). Also, applicants scored higher when their gender was opposite to the interviewers. DISCUSSION: Previous achievement and interview score had no association. CONCLUSION: Our admission interview selected different personality traits when compared to other selection tools. Medical schools should be aware of the implications of the adopted selection tools on the admitted medical student's personality because it can help providing beneficial interventions.